BIOREMEDIATION OF PETROLEUM HYDROCARBON IN CONTAMINATED SOILS: COMPARISON OF COMPOST AND WWTP SLUDGE RESIDUAL ADDITION (BIOREMEDIASI TANAH TERCEMAR PETROLEUM HYDROCARBON: PERBANDINGAN PENAMBAHAN KOMPOS DAN LUMPUR IPAL) - Cut Nanda Sari; Lina Lubnah (Testing Center for Oil and Gas LEMIGAS, 2017)
Crude oil’s processing into energy continue to increase, hence treatment for its environmental impact is needed. The objectives of the study is to determine the differences in bacteria growth rate and removal efficiency of Total Petroleum Hydrocarbon (TPH) between compost and WWTP (Waste Water Treatment Plant) sludge addition at 5% and 10% concentration levels. Those effects were acknowledged through experiments in laboratory scale using soil contaminated by 5,5% TPH within 5 weeks until it reach less than 1% as the requirement. The soil comes from Marunda Beach, compost from UPS Merdeka, WWTP sludge from Jababeka, and bacteria isolated from soil contaminated in the area surrounding refining. The treatment used in this experiment was landfarming with nutrition addition and the main variable analyzed was TPH and the microorganism population. Results of this study show that the bacteria growth rate in compost and WWTP sludge at 5% and 10% concentration each are 0,7567/weeks and 1,154/week for compost and also 0,8783/week and 1,1109/week for WWTP sludge. The TPH removal efficiency obtained was 95,32% and 96,85% for the addition of compsot as well as 91,15% and 91,02% for the addition of WWTP sludge at 5% and 10% concentrations. Base on a t-Test, the differences between all the variation of concentrations are not significant. The correlation test between TPH degradation to bacteria growth showed that there is a weak downward (negative) linear relationship. Kegiatan pengelolaan minyak bumi terus meningkat, maka dari itu dibutuhkan tindakan penanganan pemulihan kondisi lingkungan yang disebabkan oleh kegiatan tersebut. Penelitian ini bertujuan untuk mengetahui perbedaan laju pertumbuhan bakteri dan efi siensi penyisihan Total Petroleum Hydrocarbon (TPH) dengan variasi perlakuan pemberian kompos dan lumpur residu pengelolaan air limbah. Penelitian dilakukan dalam skala laboratorium dengan konsentrasi awal TPH sebesar 5,5% selama 5 minggu atau sampai TPH mencapai konsentrasi kurang dari 1% sesuai dengan baku mutu. Tanah yang digunakan berasal dari Pantai Marunda, Bekasi. Kompos berasal dari UPS (Unit Pengolah Sampah) Merdeka, Depok. Lumpur Instalasi Pengelolaan Air Limbah (IPAL) berasal dari Jababeka. Isolat bakteri yang digunakan berasal dari tanah tercemar TPH disekitar ,kilang minyak. Hasil dari penelitian menunjukkan laju pertumbuhan bakteri pada perlakuan penambahan kompos dan lumpur IPAL pada konsentrasi 5% dan 10% masing-masing adalah 0,7567/minggu dan 1,154/minggu untuk kompos, serta 0,8783/minggu dan1,1109/minggu untuk residu lumpur IPAL. Efisiensi penyisihan TPH yang diperoleh adalah 95,32% and 96,85% untuk penambahan kompos dan 91,15% dan 91,02% untuk penambahan residu lumpur IPAL pada konsentrasi 5% dan 10%. Berdasarkan hasil uji-t, perbedaan untuk masing-masing perlakuan tidaklah signifikan. Uji korelasi antara perubahan konsentrasi TPH dengan pertumbuhan bakteri menunjukkan hubungan lemah berbanding terbalik.